Memandang Bangsa dari Kota - Manneke Budiman (SUSASTRA: Jurnal Ilmu Susastra dan Budaya, 2008)
The end of the New Order era in 1998 had given birth to a new generation of young woman writers, who had played an important role in arousing readers attention to woman body and sexuality. However, an important aspect that is often forgotten in the works of those writers is the way they view the nation. Do they offer a new imagining of the nation, that is free from the heritage of the New Order integrationistic point of view? This paper discusses the works of two middle-class urban woman writers, Nukila Amal and Djenar Maesa Ayu, by focusing on how their writings were influenced by their urban experience, and how they used this experience as a stepping stone to dig possible re-imaginings of the nation. An effort to re-define nation in the framework of urbanism is shown in both Nukila's and Djenar's works; however, the question is whether the emergence of these post-reformation woman writers indicates the broken relationship with views about nation planted by the old regime, or, instead. presents an old idea dressed up in a new costume. The works which will be discussed in this paper are Cala Ibi (Nukila Amal) and Jangan Main-main (dengan Kelaminmu) (Djenar Maesa Ayu).